2013
DOI: 10.4314/tjpr.v11i6.5
|View full text |Cite
|
Sign up to set email alerts
|

Oral Methylated N-Aryl Chitosan Derivatives for Inducing Immune Responses to Ovalbumin

Abstract: Purpose: To investigate different structures of modified chitosan containing different chain lengths and aromatic moieties for vaccine delivery capacity. Methods:The characteristics of the modified chitosan, namely,Ndimethylaminobenzyl) chitosan chitosan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Methylated N-Aryl CS Derivatives An enhanced agent for in vitro paracellular permeation and in vivo adjuvant activity post oral administration to mice. Suksamran et al [185] Quaternary CS magnetic composite modified with ammonium salt and combined with iron (II and III) oxide (Fe 3 O 4 ) nanoparticles A pH-dependent bioadsorption agent for methyl orange and chromium (VI) with homogeneous monolayer chemisorption behavior process.…”
Section: Cs Derivatives Application Referencementioning
confidence: 99%
“…Methylated N-Aryl CS Derivatives An enhanced agent for in vitro paracellular permeation and in vivo adjuvant activity post oral administration to mice. Suksamran et al [185] Quaternary CS magnetic composite modified with ammonium salt and combined with iron (II and III) oxide (Fe 3 O 4 ) nanoparticles A pH-dependent bioadsorption agent for methyl orange and chromium (VI) with homogeneous monolayer chemisorption behavior process.…”
Section: Cs Derivatives Application Referencementioning
confidence: 99%
“…In addition, methylated N -(4- N , N -dimethylaminobenzyl) chitosan (TMBC), methylated N -(4- N , N -dimethylaminocinnamyl) chitosan (TMCC) and methylated N -(4-pyridinylmethyl) chitosan (TMPC) were also prepared to deliver ovalbumin (OVA) for oral vaccination. The results indicated that the TMCC showed the most efficient immune response [ 37 ]. The OVA-loaded MPs coated with TMCC by electrospray exhibited the highest in vivo adjuvant activity in both IgG and IgA immunogenicity through oral vaccination.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…These side-effects greatly decrease their immunotherapeutic efficacy and limit their clinical applications against tumors. 6,7 Thus the key issues in the stimulation of cellular immunity against tumor cells is developing new carrier materials: 8 (1) to protect the protein-based antigens/vaccines against rapid biodegradation or absorption in the bloodstream; and (2) to control the antigen processing of the vaccines inside antigen-presenting cells (APCs) through the major histocompatibility complex (MHC) I pathway.…”
Section: Introductionmentioning
confidence: 99%